Penerapan Metode Langsung dengan Media Flashcard untuk Meningkatkan Penguasaan Mufrodat Siswa Kelas VII MTsN Palopo - Kartini Kartini; Nurmiati Nurmiati; Nisa Nisa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This thesis discusses the application of direct methods using flashcard media to improve Arabic vocabulary mastery of class VII MTsN Palopo. This research aims (1) to determine the ability to master Arabic vocabulary in class VII students at Madrasah Tsanawiyah Negeri Palopo before and after applying the direct method using flashcard media. (2) to determine the effectiveness of the direct method using flashcard media in improving Arabic vocabulary mastery for class VII Madrasah Tsanawiyah Negeri Palopo. This type of research is classroom action research, the data collection method is action observation, field notes, test sheets and documentation. The results of this research are (1) classroom action research conducted by researchers. It can be concluded that the direct method using flashcard media is effective for application to class VII students (Research Class) by seeing the increase in the results of students' mastery of Arabic vocabulary which increases through the application of the direct method using flashcard media. (2) The percentage increase in cycle I can be seen that of the 40 students, 18 students completed the percentage (45%), while 22 students completed the percentage (55%). As for cycle II, it can be seen that of the 40 students, 32 students completed the percentage (80%), while 8 students did not complete the percentage (20%). From cycle I to cycle II there was an increase in learning outcomes by (25%). Thus, in cycle II the learning outcomes are said to be complete.